Peer-mediated language development in early childhood: A Vygotskian perspective on speech acquisition in children aged 4-5 years - Riska Juniar Suprihatin; Ade Dwi Utami; Erif Ahdhianto (Panicgogy International Journal, 2026)
Grounded in Vygotsky’s sociocultural theory, this qualitative single-case study examined how peer interaction supports phonological development in a 4-year-old child (Agis) with expressive speech delay. Data were collected through three months of naturalistic observation (36 sessions, ~52 hours) in playgroup and home settings, combining field notes, video recordings, photographs, and brief parental interviews. Data were analyzed through theory-guided thematic and Vygotskian discourse analysis of three focal episodes. Findings show that a more competent peer (Zura) provided modeling, phoneme segmentation, and non-judgmental correction that functioned as scaffolding within Agis’s Zone of Proximal Development, supporting progressive improvement in target phonemes (/g/, /s/, /r/) and, in one instance, transfer to a novel word in a home context. Peer-mediated practice was also associated with sustained engagement and an absence of observed distress during practice attempts. The study illustrates specific mechanisms through which peer scaffolding may support phonological learning and suggests tentative implications for inclusive early childhood practice, while findings remain exploratory given the single-case, non-comparative design.